2014
DOI: 10.4103/0028-3886.144445
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of psychiatric comorbidity, quality of life and disability in patients with migraine and tension type headache

Abstract: Psychiatric comorbidity, especially depression is common in patients with migraines and tension type headache. Quality of life and functional ability are significantly impaired in these patients. The clinician should remain aware of consequences of prolonged headache, and should provide timely intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
5
21
1
Order By: Relevance
“…Bera CS et al reported that, the psychiatric co-morbidity in subjects of migraine and TTH was 62.5% and 60% respectively with no differences between both the groups. 11 However, co-morbidities were much higher as compared to healthy controls (22.5%) in their study; Singh AK et al found that psychiatric comorbidity was seen in 53.3% of the patients presenting with chronic daily headache. 12 The most common psychiatric co-morbidity among the patients presenting with headache in our study was Mood disorders which were found to be 28%.…”
Section: Discussionmentioning
confidence: 70%
“…Bera CS et al reported that, the psychiatric co-morbidity in subjects of migraine and TTH was 62.5% and 60% respectively with no differences between both the groups. 11 However, co-morbidities were much higher as compared to healthy controls (22.5%) in their study; Singh AK et al found that psychiatric comorbidity was seen in 53.3% of the patients presenting with chronic daily headache. 12 The most common psychiatric co-morbidity among the patients presenting with headache in our study was Mood disorders which were found to be 28%.…”
Section: Discussionmentioning
confidence: 70%
“…It is seen in about 12% of population, and it is more common in women [1,2]. Migraine causes individuals to limit their daily activities because it has attacks that last for hours and even days, and these attacks cause occasional severe headaches [3,4]. Although causes that trigger migraine attacks and their mechanisms of action are not fully identified, many internal (personal) or external (environmental) factors such as hormonal changes, menstrual periods, emotional stress, hunger, fatigue, odors, noise, and sleep pattern changes trigger a migraine attack or cause an increase in headaches [5].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 According to World Health Organization (WHO), quality of life (QOL) is defined as an individual perception of his/her position in life in the context of culture and value systems and in relation to his/her goals, expectations, standards and concerns. 6,7 Researches based on clinical population have reported that migraine patients have reduced quality of life 8 when compared with age and sex matched people without migraine. 9 Also the impact of migraine on quality of life have been established in many studies.…”
Section: Introductionmentioning
confidence: 99%
“…9 Also the impact of migraine on quality of life have been established in many studies. 6 Migraine has greater impact on person's quality of life and also contributes a financial burden on health care system. 10 Assessment of patient quality of life is an important way to measure the disease burden as it has more focus on activity limitation and disabilities that occur temporarily.…”
Section: Introductionmentioning
confidence: 99%